Variations in Electrolytes Level After Del-Nido Cardioplegia Administration in Patients Undergoing Congenital Heart Defects Surgery - Noor, Mah; Asghar, Muhammad Imran; Umer, Muhammad Shoaib; Azad, Naseem; Khalil, Hafsa; Chachar, Zara (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the variation (increase or decrease) in Electrolytes level after del-nido cardioplegia administration in patients undergoing on pump congenital heart defect surgery.Study Design: The design used in this study was descriptive cross-sectional.Place and Duration of Study: The study was carried out at Pediatric Cardiac Surgery Department of Armed Forces Institute of Cardiology in Rawalpindi, Pakistan from Oct 2021 to Dec 2021.Methodology: Patients undergoing congenital heart surgery were the subject of interest in this study. The sample size was 147.Non-probability consecutive sampling technique was used. Patients undergoing on pump Congenital Heart Surgery, patients with age < 30 years, patients of both gender were included in our study. Patients with surgery of multiple stages (abdominal surgery, palliative surgery), Emergency patients, Chronic renal failure patients, Re-do operations were excluded from our study.Results: Sample size was 147 with anticipated percentage 10.7% having 78(53.1%) males and 69(46.9%) females who underwent congenital cardiac surgery. Statistical test was applied and results are significant. There was significant difference in the means of electrolyte levels after administration of Del-Nido Cardioplegia (p-value